2008
DOI: 10.1111/j.1365-2621.2007.01690.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of hydrolysates from Phaseolus lunatus seeds

Abstract: Use of low degree of hydrolysis (DH < 10%) with enzymatic treatment can produce protein hydrolysates with functional properties superior to the raw material. Suspensions of Phaseolus lunatus protein isolate (PPI) were treated with one of two commercial enzymes (Alcalase or Flavourzyme) at 50°C and pH 8.0. DH with Alcalase was greater than Flavourzyme at 5 or 15 min of reaction. Alcalase-prepared hydrolysates had more peptides than those prepared with Flavourzyme. All the hydrolysates had higher solubility than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 34 publications
(48 reference statements)
5
46
1
2
Order By: Relevance
“…Such data have been reported for several other commercial proteases acting on proteins from different legumes (Kim et al, 1990;Betancur-Ancona et al, 2009) and could be considered as a common characteristic of enzymatic reactions. Further treatment caused less intensive hydrolysis.…”
Section: Degree Of Hydrolysissupporting
confidence: 73%
“…Such data have been reported for several other commercial proteases acting on proteins from different legumes (Kim et al, 1990;Betancur-Ancona et al, 2009) and could be considered as a common characteristic of enzymatic reactions. Further treatment caused less intensive hydrolysis.…”
Section: Degree Of Hydrolysissupporting
confidence: 73%
“…Besides BPs commercialization on pharmaceuticals presentations like capsules and powders, protein hydrolysates, or purified BPs can be incorporated as “health‐enhancing” ingredients in functional foods. Pulses flours have already been studied as adjuvant ingredients into baked products, tortillas, and snacks to improve functionality and nutritional quality (Anton and others , ; Betancur‐Ancona and others ; Borsuk ). The main challenge on BP incorporation relies on their sustained activity and reaching the specific target in the organism.…”
Section: Incorporation Into Food Productsmentioning
confidence: 99%
“…Besides, the analyses of variance indicated that the variables for the two HMS samples (at 25 °C), which significantly ( P < 0.05) affected the k values, were the ratio of PH/CFG and the pH, thus with some effect on k , as observed in eqns 2 and 3; k values increase with both the ratio of PH/CFG and the pH value. Those changes observed might be explained by the protein molecular conformational changes occurring at alkaline pH values (Betancur‐Ancona et al ., ; Chel‐Guerrero et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In a previous work, it was found that nitrogen solubility of the P. lunatus protein isolate was higher and more pH dependent in Alcalase ® ‐prepared hydrolysates, than in those produced with Flavourzyme ® or in the protein isolate. Surface hydrophobicity varied conversely to the degree of hydrolysis (DH), and this characteristic was linked to technological functional properties, as even though the Flavourzyme ® ‐prepared hydrolysates were less soluble than the Alcalase ® ‐prepared ones, they had better film properties, such as high emulsifying and foaming capacities and good emulsion and foam stability (Betancur‐Ancona et al ., ).…”
Section: Introductionmentioning
confidence: 99%